Stability of Nonlinear Dirichlet BVPs Governed by Fractional Laplacian. (2nd March 2014) - Bors, Dorota
Abstract : We consider a class of partial differential equations with the fractional Laplacian and the homogeneous Dirichlet boundary data. Some sufficient condition under which the solutions of the equations considered depend continuously on parameters is stated. The application of the results to some optimal control problem is presented. The methods applied in the paper make use of the variational structure of the problem.